Genetic and Social Transmission of Parental Sex Roles in Zebra Finch Families - Morvai, Boglárka; Fazekas, Emese Alexandra; Miklósi, Ádám; Pogány, Ákos (Frontiers in Ecology and Evolution, 2022)
Parental care plays a central, reinforcing role in the evolution of sex roles and its development is often reported to be driven by genetic, rather than environmental effects. Based on these studies, however, genetic inheritance does not account fully for the often-significant phenotypic variability observed within species, a variation that we hypothesized may be explained by social effects from parents. Following a full cross-fostering design, here we aimed at disentangling genetic and social parental effects in the ontogeny of parental behaviours. Clutches of eggs were swapped, and we monitored parental behaviours in two consecutive generations of a captive population of the socially monogamous, biparental zebra finch (Taeniopygia guttata). Using nest box cameras, parental behaviour was recorded for 3 hours in two reproductive stages: on day 8 of incubation and day 10 post-hatching. These fostered birds, after becoming fully matured, received a pair randomly and we observed parental care of this second generation too, following the same protocol. We then compared various parental behaviours (such as time spent incubating, or number of nest attendances during offspring provisioning) in the second generation to those of their genetic and social parents. Based on the results of our experiment, both genetic and social effects can contribute to intergenerational transmission of specific parental behaviours, with various weights. However, the strongest and most consistent effect that we found is that of the current mate; a social effect that can manifest both in negative and positive directions, depending on the behavioural trait. Our study suggests context-specific and sexually different genetic, social and non-social environmental effects in the ontogeny of parental sex roles and outline the importance of parental negotiation in explaining individual variation of parental behaviour in biparental species.